Primary user behavior aware spectrum allocation scheme for cognitive radio networks. (February 2015) - Aslam, Saleem; Shahid, Adnan; Lee, Kyung-Geun
Abstract : Graphical abstract: Highlights: A proportional-fair oriented sharing-scheme is proposed to allocate channels. A PU activity model is developed to provide most stable channels to users. A time varying framing process is used to make variable sized frames at MAC layer. The proposed scheme reduces the delay, collisions and increases the throughput. Abstract: Cognitive radio (CR) technology can solve the problems of spectrum scarcity and low spectrum utilization. However, random behavior of the primary user (PU) appears to be an enormous challenge. In this paper, we propose a PU behavior aware joint channel selection and allocation scheme. In the first step, the channels are ranked based on statistics of the PU usage whereas in the second phase, a proportional fair oriented channel allocation scheme is employed to allocate channels among CRs. We also introduce the concept of a time-varying framing process (TVFP) that minimizes the overall data transmission time. Simulation results show that the proposed scheme outperforms existing schemes in terms of the transmission-time and the number of collisions with the PUs. In addition, it helps to save a significant amount of transmission power. Moreover, it provides a significantly higher system throughput as compared to the existing schemes.